Recent Developments of Nanofluids - Rahmat Ellahi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Over the past two decades, there has been increased attention in the research of nanofluid due to its widely expanded domain in many industrial and technological applications. Major advances in the modeling of key topics such as nanofluid, MHD, heat transfer, convection, porous media, Newtonian/non-Newtonian fluids have been made and finally published in the special issue on recent developments in nanofluids for Applied Sciences. The present attempt is to edit the special issue in a book form. Although, this book is not a formal textbook even than it will definitely be useful for research students and university teachers in overcoming the difficulties occurring in the said topic while dealing with the nonlinear governing equations. On one side the real world problems in mathematics, physics, biomechanics, engineering and other disciplines of sciences are mostly described by the set of nonlinear equations whereas on the other hand, it is often more difficult to get an analytic solution or even a numerical one. This book has successfully handled this challenging job with latest techniques. In addition the findings of the simulation are logically realistic and meet the standard of sufficient scientific value.
English
Keywords: convection; thermal radiations; viscous fluids; Nanofluid flows; thermal effects; slip; numerical and analytical techniques; porosity; magnetohydrodynamics; heat transfer; neural network